Designing Rhythmic Industrial Production - Kubaev Kazila Еrikenovich; Baisholanova, Karlygash Sovetovna (Archives of Business Research, 2017)
Rhythmic production is provided through a combination of operational planning, company’s organizational structure, and production management. We consider and use the rational operational planning based on performance estimates as a major instrument, a fundamental principle of rhythmic operation of industrial production. Operational planning and the management mechanism are linked and agreed with the planned decision to ensure continuity of rhythmic industrial production.